The Structure of a Novel Thermophilic Esterase from the Planctomycetes Species, Thermogutta terrifontis Reveals an Open Active Site Due to a Minimal ‘Cap’ Domain - Sayer, Christopher; Szabo, Zalan; Isupov, Michail N.; Ingham, Colin; Littlechild, Jennifer A. (Frontiers in Microbiology, 2015)
A carboxyl esterase (TtEst2) has been identified in a novel thermophilic bacterium, Thermogutta terrifontis from the phylum Planctomycetes and has been cloned and over-expressed in Escherichia coli. The enzyme has been characterised biochemically and shown to have activity towards small p-nitrophenyl (pNP) carboxylic esters with optimal activity for pNP-acetate. The enzyme shows moderate thermostability retaining 75% activity after incubation for 30 minutes at 70°C. The crystal structures have been determined for the native TtEst2 and its complexes with the carboxylic acid products propionate, butyrate and valerate. TtEst2 differs from most enzymes of the α/β-hydrolase family 3 as it lacks the majority of the ‘cap’ domain and its active site cavity is exposed to the solvent. The bound ligands have allowed the identification of the carboxyl pocket in the enzyme active site. Comparison of TtEst2 with structurally related enzymes has given insight into how differences in their substrate preference can be rationalised based upon the properties of their active site pockets.